Frozen-density embedding employing configuration interaction as a subsystem method. (17th June 2020) - Schieschke, Nils; Bodenstein, Tilmann; Höfener, Sebastian
ABSTRACT: We report the implementation of a general configuration interaction (CI) implementation combined with frozen-density embedding (FDE). The implemented direct CI algorithm for ground and excited states covers all truncated CI schemes ranging from CI singles (CIS) to full CI (FCI) and also the complete active-space (CAS) ansatz to treat molecules in which dynamic and static correlation effects dominate, respectively. Combining this general CI ansatz with FDE enables to study environment effects upon molecular properties, required to obtain a balanced description of correlation and environment effects. In the framework of the uncoupled FDE (FDEu) scheme, the implementation allows to combine truncated CI schemes, e.g. CI singles doubles triples quadruples (CISDTQ), embedded in water molecules computed using second-order Møller–Plesset perturbation theory (MP2) and density-functional theory (DFT), also denoted CISDTQ-in-MP2-in-DFT. GRAPHICAL ABSTRACT: